Functional annotation and identification of novel drug targets from uncharacterized proteome of Trichuris trichiura - Rauthan, Kanchan; Joshi, Saranya; Kumar, Lokesh; Kumar, Sudhir (The Journal of Infection in Developing Countries, 2025)
Introduction: Trichuris trichiura, a soil-transmitted helminth, resides in the large intestine of humans, causing an asymptomatic disease known as trichuriasis. This global health concern is particularly prevalent in low- or middle-income countries, representing a significant burden on public health as one of the most neglected tropical diseases. The diminishing effects of currently available anthelmintic drugs, attributed to escalating drug resistance, warrants an urgent need for alternative and more potent vaccines or drugs. A substantial portion of the proteins in the T. trichiura genome are uncharacterized and their annotation might offer insight into the parasite's invasion, interaction, and survival mechanisms inside the host. Hence, this study is aimed to provide functional annotations for the uncharacterized proteins identified in the proteome of T. trichiura. Methodology: The uncharacterized proteome of T. trichiura was subjected to physiological parameter computation, localization analysis, domain identification, homology, and druggability analysis. The programs used were evaluated using the Receiver Operating Characteristic (ROC) analysis. Results: Functional annotation was assigned to 165 out of the 1726 uncharacterized proteins. Out of these, 85 proteins were found to be non-homologous with the human host and considered to be potential novel drug targets. Two proteins were identified as essential proteins in the DEG database. Conclusions: Our study identified 165 new proteins from the uncharacterized proteome of the T. trichiura and several novel targets that can be further analyzed for drug designing and vaccine-related studies.